PINOY TELLS: THE TYPOLOGY OF ENGLISH LANGUAGE LEARNING STRATEGIES - Joseph Quinto; Manilyn Cacanindin (Novìtnâ Osvìta)
Despite numerous studies about language learning strategies (LLSs), many learners still misunderstand their effectiveness, thinking they require too much effort for minimal gain. Additionally, students have varied and conflicting preferences for LLSs, and factors like cultural background influence their choices, indicating a need for more research on how these elements affect learning behaviors. It is, therefore, essential to address students' perceptions and use of LLSs to ensure effective language learning. This study developed an inventory of English language learning strategies for Filipino college and university students. Using a cross-sectional exploratory sequential design, the researchers collected qualitative data from 544 Filipino university students to understand their language learning experiences and preferences, afterward developing the Typology of English Language Learning Strategies (TELLS) questionnaire through a validated thematic analysis consisting of three key components: intellective (acquiring and meaning-making), affective (information processing and acclimating), and productive (technological utilization, filtering, practicing, and validating). In the quantitative phase, 502 Filipino undergraduate respondents identified the most frequently used strategies. The results revealed that these learners commonly employed most components within the typology, except for the Practicing Productive Component. This research significantly contributes to the understanding of English language learning strategies among Filipino students. It provides a valuable resource for educators, curriculum designers, and language learning practitioners by developing an empirically validated typology tailored to students' needs and preferences. The findings also suggest avenues for future research, such as examining the relationship between TELLS components and language proficiency outcomes or exploring the implementation of TELLS in language learning.